2022
DOI: 10.3390/buildings12010051
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Embodied Carbon Emissions and Direct Construction Costs for Modular and Conventional Residential Buildings in South Korea

Abstract: Modular construction is an innovative new construction method that minimizes waste and improves efficiency within the construction industry. However, practitioners are hampered by the lack of environmental and economic sustainability analysis methods in this area. This study analyzes the embodied carbon emissions and direct construction costs incurred during the production phase of a modular residential building and provides comparison to an equivalent conventional residential building. Major drawings and desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 64 publications
0
18
0
Order By: Relevance
“…, 2015; Zhu et al. , 2018; Jang et al. , 2022), the adoption of HOSCLTs is relatively less in residential building practice (van der Ham and Opdenakker, 2021; Wuni et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…, 2015; Zhu et al. , 2018; Jang et al. , 2022), the adoption of HOSCLTs is relatively less in residential building practice (van der Ham and Opdenakker, 2021; Wuni et al.…”
Section: Introductionmentioning
confidence: 99%
“…Although prior studies have demonstrated the economic, environmental and social benefits of HOSCLTs (O'Connor et al, 2015;Zhu et al, 2018;Jang et al, 2022), the adoption of HOSCLTs is relatively less in residential building practice (van der Ham and Opdenakker, 2021; Wuni et al, 2022a, bWuni et al, 2022a. Previous studies have focused on many factors influencing adoption of HOSCLTs, where some factors are similar to those affecting LOSCLTs, but have greater effects, such as more complex process and more difficult interface coordination (Pan and Hon, 2020;Wuni et al, 2022aWuni et al, 2022bNavaratnam et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the EC within these stages is crucial in comprehending the total environmental impact generated by the concrete mixtures and steel used in the construction process. This consideration aids in making informed decisions regarding material selection, optimizing manufacturing processes, and implementing measures to reduce the overall environmental footprint of construction projects [57,66,67].…”
Section: Effect Of Embodied Carbon On Fcmentioning
confidence: 99%
“…This depiction of cost reduction across different concrete mixtures signifies the potential financial advantages and feasibility considerations associated with utilizing specific mixtures. It is important to analyze these variations comprehensively, considering not just cost but also environmental impact, structural integrity, and long-term sustainability when determining the optimal choice for a construction project [66,69].…”
Section: Cost Reduction For Concrete and Steelmentioning
confidence: 99%
“…Modular construction significantly increases productivity, offering the possibility to reduce schedules while also increasing the quality of built components [5]. It can also contribute effectively to reduce waste and, therefore, reduce the significant environmental impact of construction activities [6,7] and to provide lower life cycle costs [8]. By working in an off-site facility, there is less exposure to weather, and higher degrees of standardization and reproducibility becomes achievable while also ensuring a safer and healthier environment for the labor force [9].…”
Section: Introductionmentioning
confidence: 99%